1998
DOI: 10.1029/98jb00769
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and scattering seismic wave attenuation in the Canary Islands

Abstract: Abstract. The Canary Islands volcanic complex is studied in terms of coda wave attenuation. A multiple lapse time window method, based on the hypothesis of multiple isotropic scattering with uniform distribution of scatterers, is applied to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 40 publications
3
30
0
Order By: Relevance
“…These results are in agreement with Canas et al (1998) who found a low scattering attenuation in the Canary Islands and related the strong frequency dependence of the attenuation parameters obtained to the size of the heterogeneities in the region, which would be at least comparable to the wavelength of the lowest analyzed frequencies, or about 2.6 km.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…These results are in agreement with Canas et al (1998) who found a low scattering attenuation in the Canary Islands and related the strong frequency dependence of the attenuation parameters obtained to the size of the heterogeneities in the region, which would be at least comparable to the wavelength of the lowest analyzed frequencies, or about 2.6 km.…”
Section: Discussionsupporting
confidence: 81%
“…This result may indicate that random inhomogeneity in the Canary Islands region is represented by a Gaussian ACF. An analogous conclusion was reached by Canas et al (1998) who separately estimated the contribution of intrinsic absorption and scattering to total attenuation using an independent data set in the same region. They found that the decrease of scattering attenuation was faster than with increasing frequencies, which implies that the medium may be characterized by a Gaussian ACF (Wu, 1985).…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations